2022
DOI: 10.1111/apha.13862
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles and microRNAs are altered in response to exercise, insulin sensitivity and overweight

Abstract: Extracellular vesicles induced by exercise have emerged as potential mediators of tissue crosstalk. Extracellular vesicles and their cargo miRNAs have been linked to dysglycemia and obesity in animal models, but their role in humans is unclear. Aim:The aim of the study was to characterize the miRNA content in plasma extracellular vesicle isolates after acute and long-term exercise and to study associations between extracellular vesicle miRNAs, mRNA expression in skeletal muscle and adipose tissue, and cardiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 67 publications
0
24
0
Order By: Relevance
“…The finding that EPS increases miR-320b might therefore be noteworthy. Several studies on exercise and plasma EVs have been reported ( Estebanez et al, 2021 ; Doncheva et al, 2022 ). The review by Estebanez et al summarized results of released exosome miRs in plasma after four different exercise protocols ( Estebanez et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that EPS increases miR-320b might therefore be noteworthy. Several studies on exercise and plasma EVs have been reported ( Estebanez et al, 2021 ; Doncheva et al, 2022 ). The review by Estebanez et al summarized results of released exosome miRs in plasma after four different exercise protocols ( Estebanez et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this latter study, they additionally revealed that exercise evoked EVs could transfer their protein content into the liver, implying a role in tissue crosstalk during exercise. Also, the level of miRs in plasma EVs increased by exercise in a group of sedentary men ( Doncheva et al, 2022 ). However, the origin of plasma EV is manifold, and the contribution of skeletal muscle EVs is unknown, although, it has been suggested that about 5% of plasma EVs are derived from skeletal muscles ( Estrada et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acute exercise can increase several miRNAs (including miR-652-3p) in extracellular vesicles, which were associated with insulin sensitivity and adiposity. 10 Type 2 diabetes is characterized by insulin resistance coupled with insufficient glucose uptake by muscle and fat and unrestricted hepatic glucose production. This results in hyperglycemia.…”
Section: Hormones-modulators Of Metabolismmentioning
confidence: 99%
“…Extracellular vesicles can function as components in cell–cell and tissue‐tissue communication and they are implicated in immune responses and insulin resistance. Acute exercise can increase several miRNAs (including miR‐652‐3p) in extracellular vesicles, which were associated with insulin sensitivity and adiposity 10 …”
mentioning
confidence: 99%
“…In this issue of Acta Physiologica , Doncheva et al 1 advance our understanding of biomarkers that reflect tissue‐specific cardiometabolic disease. They did so by measuring circulating miRNAs within extracellular vesicles (EVs) regulated by exercise in human plasma and defining their associations with the transcriptome of metabolically active tissues during obesity.…”
mentioning
confidence: 99%